Antibody Responses and the Vaccine Efficacy of Recombinant Glycosyltransferase and Nicastrin Against Schistosoma japonicum - Bowen Dong; Haoran Zhong; Danlin Zhu; Luobin Wu; Jinming Wang; Hao Li; Yamei Jin (Pathogens)
Schistosomiasis is a neglected tropical disease and the second most common parasitic disease after malaria. While praziquantel remains the primary treatment, concerns about drug resistance highlight the urgent need for new drugs and effective vaccines to achieve sustainable control. Previous proteomic studies from our group revealed that the expression of Schistosoma japonicum glycosyltransferase and nicastrin as proteins was higher in single-sex males than mated males, suggesting their critical roles in parasite reproduction and their potential as vaccine candidates. In this study, bioinformatic tools were employed to analyze the structural and functional properties of these proteins, including their signal peptide regions, transmembrane domains, tertiary structures, and protein interaction networks. Recombinant forms of glycosyltransferase and nicastrin were expressed and purified, followed by immunization experiments in BALB/c mice. Immunized mice exhibited significantly elevated specific IgG antibody levels after three immunizations compared to adjuvant and PBS controls. Furthermore, immunization with recombinant glycosyltransferase and nicastrin significantly reduced the reproductive capacity of female worms and liver egg burden, though egg hatchability and adult worm survival were unaffected. These findings demonstrate that recombinant glycosyltransferase and nicastrin are immunogenic and reduce female worm fecundity, supporting their potential as vaccine candidates against schistosomiasis.